(untitled) (Journal of Science and Technology, 2016)
Tamale, like all the major cities in Ghana is confronted with a myriad of challenges. These challenges range from housing development without planning permission, sprawl and consequent suburban development. Based on a case study approach within the qualitative research methodology, a total of 738 adult population from four sectors in Tamale were sampled and interviewed to solicit their views on land, architecture, urban sprawl and suburban development in Tamale. This study in conclusion recommends an integrated approach to address architectural, land management and planning issues for the benefit of land and property owners as well as providing prospective developers access to land to enhance the economic and physical image of Tamale as an evolving metropolis